2014
DOI: 10.3390/molecules190914235
|View full text |Cite
|
Sign up to set email alerts
|

Constituents of the Roots and Leaves of Ekebergia capensis and Their Potential Antiplasmodial and Cytotoxic Activities

Abstract: Abstract:A new triterpenoid, 3-oxo-12β-hydroxy-oleanan-28,13β-olide (1), and six known triterpenoids 2-7 were isolated from the root bark of Ekebergia capensis, an African medicinal plant. A limonoid 8 and two glycoflavonoids 9-10 were found in its leaves. The metabolites were identified by NMR and MS analyses, and their cytotoxicity was evaluated against the mammalian African monkey kidney (vero), mouse breast cancer (4T1), human larynx carcinoma (HEp2) and human breast cancer (MDA-MB-231) cell lines. Out of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
37
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 29 publications
0
37
0
Order By: Relevance
“…Little is known on the antimicrobial activities of this plant, but Sewram et al, (2000) reported that compounds isolated from this plant showed uterotonic activities against both pregnant and non pregnant guinea pig uterine smooth muscle. However, compounds previously isolated from the genus Ekebergia such as terpenoids; oleanonic acid, 12 , ekeberin A, 13 , flavonoids; kaempferol-3-O-β- d -glucopyranoside, 14 , quercetin-3-O-β- d -glucopyranoside, 15 (Irungu et al, 2014;) could be the reason why these extracts showed good antimycoplasmal activities against all the strains tested
.…”
Section: Discussionmentioning
confidence: 97%
“…Little is known on the antimicrobial activities of this plant, but Sewram et al, (2000) reported that compounds isolated from this plant showed uterotonic activities against both pregnant and non pregnant guinea pig uterine smooth muscle. However, compounds previously isolated from the genus Ekebergia such as terpenoids; oleanonic acid, 12 , ekeberin A, 13 , flavonoids; kaempferol-3-O-β- d -glucopyranoside, 14 , quercetin-3-O-β- d -glucopyranoside, 15 (Irungu et al, 2014;) could be the reason why these extracts showed good antimycoplasmal activities against all the strains tested
.…”
Section: Discussionmentioning
confidence: 97%
“…Some of the pharmacological activities of E. capensis listed in literature include acetylcholinesterase-inhibitory [57], analgesic and anti-inflammatory [26,69,70], anthelmintic [55,71], antibacterial [25,51,56,72,73], antigonococcal [25,67], antimycobacterial 74], antimycoplasmal [47], antifungal [25,56,72,73], antihypertensive [19,75], antioxidant [27,57,68,76], antimalarial and antiplasmodial [33,34,58,59,[77][78][79], antischistosomal [80], antitrypanosomal [81], and antiviral [25,60] and cytotoxicity [26,34,59,60,76,[82][83][84] activities. These pharmacological activities of various parts of the species are summarized below.…”
Section: Pharmacological Activities Of E Capensismentioning
confidence: 99%
“…The Ames test revealed that all leaf extracts were non-mutagenic toward S. typhimurium strain TA98 but bark extracts induced 50.0 revertant colonies at 500 µg/ml and 50.0 µg/ml and there was no dose-dependent increase and; therefore, the extract could be classified as a weak mutagen[26]. Irungu et al[59] evaluated the cytotoxicity activities of leaf and root extracts of E. capensis and compounds6,7,16,22,23,25,28,41, and 42isolated from the species against the mammalian African monkey kidney (vero), mouse breast cancer (4T1), human larynx carcinoma (HEp2), and human breast cancer (MDA-MB-231) cell lines using MTT assay. The leaf and root extracts exhibited activities against vero, 4T1 and HEp2 with IC 50 values ranging from 2.8 µM to 97.8 µM while compounds 42, 25, 23, and 22 showed activities with compound 42 with the highest cytotoxicity with IC 50 values of 1.4 µM and 13.3 µM against the HEp2 and 4T1 cells, respectively[59].…”
mentioning
confidence: 99%
See 2 more Smart Citations